A preliminary study to determine the diagnostic reference level using dose–area product for limited-area cone beam CT - Endo, A (The British Institute of Radiology., 2013)
OBJECTIVES: The aim of this study was to measure the dose–area product (DAP) of limited-area cone beam CT (CBCT) units used by dental offices, and to evaluate the rationale of the DAP with an aid of optically stimulated luminescence (OSL) dosemeter in measuring radiation dose. METHOD: The DAPs of 21 CBCT units used in the dental offices of Tokyo and the surrounding areas from five different manufacturers were measured using OSL nanoDot dosemeter. An assembly of OSL dosemeters with an X-ray film was exposed by CBCT units at exposure parameters commonly used in each dental office. DAP values were then calculated as expressed in mGy cm(2). RESULTS: DAP values ranged from 126.7 mGy cm(2) to 1476.9 mGy cm(2), depending on the units used. CONCLUSION: OSL dosemeter coupled with film can be utilized for a large-scale study to measure DAP. The DAP values for individual CBCT units depend not only on the field of view, but also on the exposure parameters adapted by the dental offices.